MOLECULAR MODELING AND IN SILICO HUMAN AND ENVIRONMENTAL TOXICOLOGICAL STUDY FOR THE ANTIBIOTICS TRIMETHOPRIM AND SULFADOXINE - Araujo, Laura Faria; Rosa, José Felipe Leite Ferreira; Prates, Ludmilla Louise Cerqueira Maia; Motta, Luiz Frederico (Seven Editora, 2025)
Sulfadoxine in combination with trimethoprim are commonly used for broad-spectrum antimicrobial therapy in veterinary medicine. Although widespread resistance limits use in ruminants, the combination is still useful in the treatment of gastrointestinal and respiratory infections in calves, including neonatal colibacillosis. The pharmacokinetic profile of sulfadoxine and trimethoprim differs from each other due to their chemical properties: sulfadoxine acts as a weak acid while trimethoprim is a weak base, thus concentrating at different sites in the body. Sulfadoxine and trimethoprim are two antimicrobial agents that are often used in combination due to their different mechanisms of action, acting synergistically against bacterial infections. The package inserts, both from national and international companies, state that the pharmaceutical product containing the two antibiotics has as its target the treatment of respiratory and gastrointestinal diseases in cattle and horses. One of the major challenges is related to the fact that antibiotics produced by the pharmaceutical industry result in antibiotic residues in the environment, both in water bodies and in the soil. These residues contaminate the food chain, affecting fish, crustaceans and even organisms such as Tetrahymena pyriformis, a protozoan widely distributed in freshwater environments. This contamination mechanism is very worrying because it not only compromises the health of ecosystems, but will also affect the humans who consume the contaminated food. The in silico toxicological study revealed that the compounds did not present toxicity in the AMES test, did not present carcinogenicity and did not have Acute Oral Toxicity. DOI: https://doi.org/10.56238/sevened2024.037-135